Receiving financial support and its association with late-age depression: The mediating role of social engagement - Keying Song; Zijian Zhao; Amiya Saha; Jhumki Kundu (Experimental Gerontology)
Objectives: Researchers have long been concerned with the association between family financial support and depression in older adults. However, it remains unclear whether social engagement influences the relationship between depression and financial support in later life. Therefore, this study aims to examine the relationship between receiving financial support from family and others and depression among Indian older adults and to also explore the mediating effect of social engagement on this relationship. Subjects and methods: Data from the Longitudinal Aging Study in India Wave 1 (2017–2018) was used for the empirical analysis. A total sample of 30,210 older adults aged 60 years and above were selected for the study. The study employs bivariate and binary logistic regression analysis. Further Karlson–Holm–Breen method was adopted for mediation analysis. Results: The adjusted prevalence of depression among older adults who did not receive financial support from family or others was nearly 33.8 % (men: 29.8 %, women: 37.4 %), compared to 29.9 % for those who received support (men: 27.6 %, women: 32 %). Older adults who received financial support had 21 % lower odds of depression (AoR: 0.79; 95 % CI: 0.73, 0.84) than those who did not. Additionally, the association between depression and receiving financial support was mediated by social engagement (17.3 %) with the mediating effect being higher among older women (29.3 %) than older men (13.5 %). Conclusion: The study advances that although financial support plays a significant role in reducing depressive symptoms in older adults, social engagement also serves as an important mediator in this relationship. Enhancing opportunities for social engagement may amplify the protective effects of financial support, offering a more comprehensive approach to addressing mental health challenges among aging populations in India.